Expatriate effectiveness: from conceptualization to operationalization. (December 2022) - Chen, Xiaowen; Moon, Nicholas A; Davy, Alexander Kade; Hong, Julia; Gabrenya, William K
Expatriate effectiveness has been studied extensively in the expatriate literature. Despite its popularity, the construct has not been well-defined or properly operationalized. Adopting a performance perspective, we conceptualize expatriate effectiveness in terms of task, contextual, and adaptive performance. The relative importance of each type of performance may vary across expatriate jobs and over the course of the expatriate's tenure. We propose six operational and implementation guidelines for expatriate effectiveness measurement in the contexts of the nature of the expatriate job, the prioritized performance at each stage of adjustment, rater sources and capabilities, rater culture, frequency of evaluation, and the fit between measurement methods and criteria. We contribute to cross-cultural management research by providing a thorough description of the criterion issues in this literature, offering a conceptual framework to differentiate and integrate a variety of constructs that reflect different aspects of cross-cultural effectiveness, and calling attention to the influential role of measurement operations and implementation for the validity of research studies.